2016
DOI: 10.1167/iovs.16-19871
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Chronic Loss of Optic Nerve Axons and the Effects on the Retinal Nerve Fiber Layer Structure in Primary Disorder of Myelin

Abstract: PurposeWe determined whether the chronic lack of optic nerve myelination and subsequent axon loss is associated with optical coherence tomography (OCT) changes in the retinal nerve fiber layer (RNFL), and whether this models what occurs in multiple sclerosis (MS) and confers its use as a surrogate marker for axon degeneration.MethodsUsing an animal model of Pelizaeus-Merzbacher disease (shp) bilateral longitudinal measurements of the peripapillary RNFL (spectral-domain OCT), electroretinograms (ERG), and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…Diffusion weighted imaging provides an alternative approach to early evaluation of glaucoma, a group of diseases characterized by the loss of RGCs and their axons. The technique we describe does overcome a major limitation associated with OCT, which is increasingly reported in the veterinary literature for assessment of the retina and ONH 46‐63 . Canine glaucoma is commonly associated with corneal opacities and drug‐induced miosis which both preclude reliable OCT assessment, but do not affect measurements of the white matter tracts using DTI.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging provides an alternative approach to early evaluation of glaucoma, a group of diseases characterized by the loss of RGCs and their axons. The technique we describe does overcome a major limitation associated with OCT, which is increasingly reported in the veterinary literature for assessment of the retina and ONH 46‐63 . Canine glaucoma is commonly associated with corneal opacities and drug‐induced miosis which both preclude reliable OCT assessment, but do not affect measurements of the white matter tracts using DTI.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are impaired in HET mice and almost absent in KOs , suggesting a key role for Nr2f1 in the maturation of oligodendrocytes and in the myelination process, consistently with a previous report (Yamaguchi et al, 2004 ). Hypomyelination could in turn exacerbate the loss of ON axonal fibers by affecting RGC survival (Teixeira et al, 2016 ). It would be interesting to investigate whether this is a common mechanism happening in other structures, for example in the neocortical white matter, since MRI scans have revealed impaired myelination in some BBSOAS patients (Chen et al, 2016 ; Rech et al, 2020 ).…”
Section: Astrogliosis and Hypomyelination Converge To Optic Nerve Atrophy In A Nr2f1 -Deficient Modelmentioning
confidence: 99%
“…[23][24][25][26] Despite widespread use of OCT in clinical ophthalmic and optometry settings for people, the use of OCT for assessment of the canine posterior segment remains limited, although its use has been increasingly reported over the last decade. Veterinary use of OCT for assessment of the posterior segment is reported in normal Beagles, 27,28 dogs with Sudden Acquired Retinal Degeneration Syndrome (SARDS), [29][30][31] in research settings investigating diseased retinas, [32][33][34][35][36] in cats, 37,38 and in case reports describing a variety of retinal conditions. 39- 42 Grozdanic et al 43 reported thinning of the inferior retina as measured by OCT following induction of an acute elevation in IOP in normal Beagles.…”
Section: Author Manuscriptmentioning
confidence: 99%